Poly(β‐amino ester)‐co‐poly(caprolactone) Terpolymers as Nonviral Vectors for mRNA Delivery In Vitro and In Vivo. Issue 14 (14th May 2018) - Capasso Palmiero, Umberto; Kaczmarek, James C.; Fenton, Owen S.; Anderson, Daniel G.
Abstract: The production of new proteins with messenger RNA (mRNA) has gained a broad interest due to its potential for addressing a wide range of diseases. Here, the design and characterization of novel ionizable poly(β‐amino ester)‐ co ‐poly(caprolactone) terpolymers, synthesized via the combination of the ring opening polymerization and the Michael step‐growth polymerization, are reported. The versatility of this method is demonstrated by varying the number of caprolactone units attached to each poly(β‐amino ester) (PBAE) terpolymer. The ability of the novel poly‐caprolactone (PCL)‐based PBAE materials to deliver mRNA is shown to depend on the physiochemical characteristics of the material, such as lipophilicity, as well as the formulation method used to complex the polymer with the oligonucleotide. This latter variable represents a previously unstudied aspect of PBAE library screens that can play an important role in identifying true top candidates for nucleic acid delivery. The most stable terpolymer is injected intravenously (IV) in mice and shows a transfection efficacy several times higher than the polyethylenimine (PEI) which is focused in the spleen, opening the possibility to use these biodegradable carriers in the intravenous delivery of antigen‐encoding mRNA for cancer immunotherapy and vaccination. Abstract : Ionizable poly(β‐amino ester)‐ co ‐poly (caprolactone) terpolymers are synthesized via the combination of the ring opening polymerization and the Michael step‐growth polymerization. The versatility of this method allows for the production of mRNA delivery carriers with high transfection efficiency that depends on the material physiochemical characteristics. These terpolymers are a promising platform for the intravenous delivery of therapeutic mRNA to the spleen.